A argumentação e o político no texto jurídico : a imprensa numa ação indenizatória - Silva, Maria Fernanda Faccipieri (2009)
This study is developed under the theoretical-methodological perspective of Semântica do Acontecimento, and its objective is to understand the function of argumentation and designation in the language, more specifically, analyze how juridical argumentation works. Our object of analysis was a lawsuit characterized as Indemnity Action3, through which the petitioners request the closure of a website where they were offended anonymously and the consequent indemnity payment. Firstly, we established two cenas enunciativas from the corpus characterized by the court cena and the website cena, composed of smaller cenas. Through this analysis, we could observe how argumentative orientation happens when mobilizing the speakers and the memoráveis present, as well as establish how the anonymity in this cena enunciativa works. For that, we established a relation between silence and rumor, studied by Orlandi4 (mmeo) and the anonymity present in court. It was possible, therefore, to conclude from the characterization of the cena the nonexistence of this anonymity. Secondly, we used the concept of Domínio Semantico de Determinação to observe how the designation of Court, space that moves the action, takes place. We observed a relation of antonymy in its designation, which characterizes it either as a space for offenses or as a space for indictment, and that, through the designations and the memoráveis, orient the argumentation to the advantage of the website closure, as well as indemnity payment to the petitioners.